Characteristics and quality of freeze-dried mango powder pre-frozen at different temperatures - Capariño, Ofero A. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2000)
Aseptically processed mango puree was first frozen at either -40 C or -65 C using an ultra-low temperature freezer, or at -192 C by direct immersion in liquid nitrogen. All samples were then freeze-dried at a vacuum pressure of 0.001-0.05 Torr.